Răspunsuri

2014-08-07T02:10:04+03:00
1)-(-8) + (-2) + (+15) +(-21)= +8 -2 +15 -21=  23 -23=0

2)(-13+18)- [-(-4+5)+(-8+3)-(-8-3)]=

= +5 -[-(+1) -(+5)-(-11)]=

= 5 -(-1-5+11)=

=5 -(-6+11)=

=5-(+5)=

= 5 -5 =0

3) -8-3+ (11-20) * (-2+5)=

= -11 +( -9) * (+3)=

= -11 + (-27)=

= -11-27=  -38

4) -4-(-13+8) * (-42+35 -11)=

= -4 - (-4) * ( -53+35)=

= -4 - (-4) * ( -18)=

= -4 - ( +72)=

= -4-72=  -76

5) (-7) * (-6)  + (-2-6) * (-4-5)=

= (+42) + (-8) * (-9)=

= 42 + (+72)=

= 42+72= 114

6) (-3) * [ (-12) : (-2-4)] - (-28+19)=

= (-3) * [(-12) : (-6)] - ( -9)=

= (-3) * (+2)  +9=

= -6 +9= 3

7) 2¹¹ : (7 * 2⁸ +2⁸)=

= 2¹¹ : [ 2⁸( 7+1) ]=

= 2¹¹ : (2⁸ *8)=

= 2¹¹ : (2⁸  *  2³)=

= 2¹¹ :2¹¹

= 2⁰  =1

8) [ -20⁴⁰  * (-3³ )¹³ ]  : (-6)³⁹=

= [  -20⁴⁰ * (-3)³⁹]  : (-6)³⁹=

= ( 60 )⁷⁹ : ( -6) ³⁹ =

= (-10)⁴⁰ =10⁴⁰

9) 8x+16=0

8x= -16

x= -16/8

x= -2

10) 7x -3 = 2(x+6)

7x-3= 2x+12

7x-2x =12+3

5x = 15

x= 15/5 =3
3 2 3